Preventive approaches to perineal trauma in vaginal delivery: Systematic Literature Review - Kunkel, Maria Elizete (2024)
BACKGROUND: The female pelvic floor plays a crucial role in supporting the pelvic organs during vaginal delivery and sexual practice. Often, the changes that occur during pregnancy do not prevent injuries during vaginal childbirth, contributing to the manifestation of dysfunctions such as urinary incontinence and prolapse. Studies highlight the importance of pelvic floor exercises as a preventative measure, with massage, specific exercises, and the use of vaginal dilator devices. However, there is a need to conduct additional research to validate the effectiveness of these approaches. AIM: To conduct a Systematic Literature Review (SLR) to investigate the scientific evidence that addresses strategies aimed at preventing perineal injury in vaginal delivery. METHOD: The search for studies was conducted on the PubMed, LILACS, Scopus, and Elsevier databases, following a PICOC protocol. The search strategy was developed in each database using MeSH terms and keywords, according to PRISMA guidelines. RESULTS: Of the 96 titles initially found, 21 articles remained after evaluation according to the inclusion and exclusion criteria. Pelvic physiotherapy stands out in the preparation for childbirth by strengthening and increasing the resistance of the muscles in the pelvic region. There are physical and emotional benefits, resulting in more peaceful birth experiences. Vaginal dilator devices are effective in reducing episiotomies, perineal trauma, and lacerations. CONCLUSION:The research points to the need for future studies to explore pregnant women's experiences in depth, including acceptability and comfort. The effectiveness of vaginal dilator devices, perineal exercises, and perineal massage in preventing perineal trauma during normal childbirth is highlighted.